2012
DOI: 10.1136/bmjqs-2011-000213
|View full text |Cite
|
Sign up to set email alerts
|

Can patients report patient safety incidents in a hospital setting? A systematic review

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 41 publications
6
140
1
2
Order By: Relevance
“…7,26 These results further contradict studies specific to cancer patients which found that the longer duration of care in a cancer centre increased the likelihood of patients reporting concerns about safety. 27,28 However, this study differed from other studies as its design enabled patients to report incidents, rather than patients responding to questions asked by researchers, hence the method employed may account, at least in part, for the differences in results.…”
Section: Number and Type Of Incidents Reportedcontrasting
confidence: 55%
“…7,26 These results further contradict studies specific to cancer patients which found that the longer duration of care in a cancer centre increased the likelihood of patients reporting concerns about safety. 27,28 However, this study differed from other studies as its design enabled patients to report incidents, rather than patients responding to questions asked by researchers, hence the method employed may account, at least in part, for the differences in results.…”
Section: Number and Type Of Incidents Reportedcontrasting
confidence: 55%
“…It included systematic reviews of articles on the most effective ways of engaging the public in patient safety and evidence scans or reviews of the type and extent of patient involvement that might be considered in patient safety Hall et al 2010;Doherty and Stavropoulou 2012;Ward and Armitage 2012;Coulter and Ellins 2007;Schwappach 2010;Davis et al 2012). Such reviews tended not to offer much evidence for the effectiveness of patient and public involvement in patient safety; reviews by the Health Foundation (2013) and Hall et al (2010) struggled to determine from the extant literature what works best in engaging patients in terms of safety outcomes.…”
Section: The Literaturementioning
confidence: 95%
“…There are some exceptions to this -for example Ward and Armitage (2012) explore the extent of safety incident reporting among patients in a hospital setting, Weingart et al (2004) report on lessons learnt from an intervention to prevent adverse drug events, and Larsen et al (2011) describe the use of patient feedback in real time to improve safety. In general, though, the published evidence focuses on attitudes and expectations rather than on the opportunities for patient involvement in patient safety and the results of these.…”
Section: The Literaturementioning
confidence: 96%
“…attitudes, values, emotions, behaviours and interactions of patients) suggests patients should be integrated into safety assessments, with patient accounts of good or poor care being used to detect unsafe organisational cultures [27] [28]. Patient perspectives have therefore been linked with patient safety and clinical effectiveness across a wide variety of treatments, settings, population groups and outcome measures [29].…”
Section: Organisational Culturementioning
confidence: 99%